Goods and Service Tax (GST) on Indian Economy - Bansal, Vipul; Bhatia, Shubhra (IJRDO - Journal of Business Management, 2017)
Goods and Services Tax is defined as the Giant Indirect Tax structure designed to support and enhance the economic growth of a country. More than 150 countries have implemented GST so far. However, the idea of GST in India was mooted by Vajpayee government in year 2000 and the constitutional amendment for the same was passed by the Loksabha on 6th May 2015 but is yet to be ratified by the Rajyasabha. It would be interesting to understand why this proposed GST regime may hamper the growth and development of the country.